The Trend towards Digital Transformation: Fatality or Choice? - Afif, Hana; Khouloufi, Wahiba (Finance and Business Economies Review, 2022)
This study is summarized in answering a problem centered on the possibility of considering digital orientation an inevitable necessity or an option adopted by countries, as it aims to clarify the concept of digital transformation and its stages, identify the reasons for going towards it, and analyze the reality of digital transformation in the African continent. This study concluded that digital transformation requires funding, human resource efficiency, and an adequate infrastructure, in addition to the fact that the digital transformation strategy in Africa bears weaknesses such as lack of coordination between continental institutions, lack of funding, guidance and training provided to digital entrepreneurs, and in order to achieve Digital transformation requires training human resources in order to improve their performance in this field, and to provide the necessary environment.